2019
DOI: 10.1007/s00125-019-05015-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of diabetes prevention on mortality and future burden of dementia and disability: a modelling study

Abstract: Aims/hypothesisDiabetes is associated with an increased risk of dementia. We estimated the potential impact of trends in diabetes prevalence upon mortality and the future burden of dementia and disability in England and Wales.MethodsWe used a probabilistic multi-state, open cohort Markov model to integrate observed trends in diabetes, cardiovascular disease and dementia to forecast the occurrence of disability and dementia up to the year 2060. Model input data were taken from the English Longitudinal Study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…A record of a marker such as psychosis within the Severe Neuropsychiatric domain increased risk of all outcomes, concordant with a previously identified link of behavioural and psychological symptoms and/or antipsychotic use with risk of hospitalisation, nursing home admission, and mortality [28–31]. The Increased Multimorbidity, Comorbidity, and Symptoms domains were commonly recorded and strongly associated with the outcomes, supporting reviews showing increases in comorbidity and health‐related burden related to poor dementia outcomes [30,32,33]. The Care domain showed associations across all outcomes; research shows that caregiver coping and stress is associated with poor outcomes in the person with dementia [30,34], but also will be reflective of increased provision of care as demonstrated by the strong association with palliative care.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…A record of a marker such as psychosis within the Severe Neuropsychiatric domain increased risk of all outcomes, concordant with a previously identified link of behavioural and psychological symptoms and/or antipsychotic use with risk of hospitalisation, nursing home admission, and mortality [28–31]. The Increased Multimorbidity, Comorbidity, and Symptoms domains were commonly recorded and strongly associated with the outcomes, supporting reviews showing increases in comorbidity and health‐related burden related to poor dementia outcomes [30,32,33]. The Care domain showed associations across all outcomes; research shows that caregiver coping and stress is associated with poor outcomes in the person with dementia [30,34], but also will be reflective of increased provision of care as demonstrated by the strong association with palliative care.…”
Section: Discussionsupporting
confidence: 75%
“…This study aimed to determine the validity of markers and domains as indicators of progression, and not as independent predictors of poor outcome. As such, some of the associations identified with long‐term outcomes may have arisen through chance given the multiple testing, and there may be other factors predictive of poor outcome, including socioeconomic status, ethnicity, social support, and social care provision [24,30,32,33,48,49], and measures obtainable by invasive testing such as pathogen presence (e.g., cerebrospinal fluid t‐tau) and cortical atrophy (volumetric magnetic resonance imaging). Future prognostic research should assess which domains improve prediction of long‐term outcomes when added to other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary imbalances may trigger metabolic disorders and obesity, which in the long-term may progress to insulin resistance and T2D. Clinical studies set obesity and associated metabolic derangements as important risk factors for dementia (Pedditzi et al, 2016;Singh-Manoux et al, 2018;Bandosz et al, 2020). Li et al (2017) observed that cortical Aβ deposition by [ 18 F]-florbetapir PET was decreased in T2D patients while Aβ levels increased in the cerebral spinal fluid.…”
Section: Introductionmentioning
confidence: 99%
“…However, other preventable NCDs generally have longer latency. 176,177 Therefore, the full benefit of increased Health Check interventions might only be realised beyond the 20 years horizon set in our simulations, and further preventative actions at individual and population level might be needed.…”
Section: Discussionmentioning
confidence: 99%